FRI0279 Anemic hypoxia is associated with pulmonary arterial hypertension in patients with systemic lupus erythematosus. (23rd January 2014) - Kim, K.-J.; Baek, I.-W.; Yoon, C.-H.; Choi, J.-J.; Kim, W.-U.; Cho, C.-S.
Abstract : Background: Pulmonary arterial hypertension (PAH) is a serious and often fatal complication of systemic lupus erythematosus (SLE), but its pathogenesis is still unclear. Hypoxia-induced pulmonary vascular remodelling has been suggested to be a crucial mechanism for PAH. Objectives: To investigate the association between anemic hypoxia and PAH in patients with SLE. Methods: A post hoc analysis was performed of the prospective cross-sectional study to determine the PAH in 116 patients with SLE. PAH was defined as resting pulmonary artery systolic pressure (PASP) ≥ 40 mmHg by echocardiography. Duration of anemia was calculated as cumulative months of anemia (defined by hemoglobin [Hb]<10 g/dL) during the preceding years. Oxygen delivery (DO2 ) was estimated by the product of cardiac output (CO) and arterial oxygen content (CO x %Saturation x 1.39 x Hb). Serum IL-6 level and plasma N terminal-pro B-type natriuretic peptide (NT-proBNP) were also quantified. Results: Among 116 SLE patients, PAH was detected in 11 patients (9.5%). The range of PAH was 40.4-90 mmHg. Twenty-one patients (18.1%) showed PASP of 30-40 mmHg. Compared to patients without PAH, patients with PAH had lower Hb levels (9.8±0.5 versus 11.9±0.2 g/dL, P =0.001), but longer duration of anemia during the preceding 1, 2, and 3 years, respectively (all P< 0.05). Importantly, DO2 value of patients with PAH were significantly lower than those of patients without PAH (7.9±0.8 versus 10.0±0.2 ml/min/kg, P =0.006). Moreover, DO2 value inversely correlated with PASP and serum NT-proBNP levels (Y=-0.241, P =0.013 and Y=-0.292, P =0.001, respectively). In multivariate regression analysis, duration of anemia was independently associated with the presence of PAH in SLE patients ( P =0.006). When patients were divided into three groups according to tertiles of Hb well as PASP, serum IL-6 significantly increased across the tertiles of PASP ( P for trend=0.038), but decreased across the tertiles of Hb ( P for trend=0.001). Conclusions: Our study suggests that prolonged exposure to anemic hypoxia, which is associated with increased serum IL-6, might be a component of pathogenesis of PAH in SLE patients. Acknowledgements: Nothing specified. Disclosure of Interest : None Declared